Devolatilization Studies of Oil Palm Biomass for Torrefaction Process through Scanning Electron Microscopy. Issue 1 (March 2016) - Daud, D.; Rahman, A. Abd.; Shamsuddin, A.H.
Abstract: In this work, palm oil biomass consisting of empty fruit bunch (EFB), mesocarp fibre and palm kernel shell (PKS) were chosen as raw material for torrefaction process. Torrefaction process was conducted at various temperatures of 240 °C, 270 °C and 300 °C with a residence time of 60 minutes. The morphology of the raw and torrefied biomass was then observed through Scanning Electron Microscopy (SEM) images. Also, through this experiment the correlation between the torrefaction temperatures with the volatile gases released were studied. From the observation, the morphology structure of the biomass exhibited inter-particle gaps due to the release of volatile gases and it is obviously seen more at higher temperatures. Moreover, the change of the biomass structure is influenced by the alteration of the lignocellulose biomass.